Advertising Agrarian Unreality: College Students' Preferences for Agricultural Commodity Advertising Content - Annie R. Specht; Emily B. Buck (Journal of Applied Communications, 2014)
Critics of agricultural commodity groups claim the advertising strategies used by those groups promote unrealistic perceptions of modern agricultural practices. To answer this question, the researchers sought to investigate young consumers’ preferences for realistic versus unrealistic agricultural video content. Using an online survey questionnaire, the researchers compared undergraduate students’ affective responses to content from the “Happy Cows” advertising campaign to those elicited from viewing educational video content pertaining to modern dairy husbandry practices. Subjects reported similar levels of liking for both video sets, while the informational videos scored higher for realism and perceived quality of animal care. Students with less familiarity with agriculture reported greater liking for the educational content. The researchers recommend a movement away from purely entertaining advertising content for agricultural products in favor of more realistic, fact-based promotions.
Keywords: Uses and gratifications; visual imagery; schema congruity; advertising; dairy